(untitled) (Research, Society and Development, 2020)
The Rosário Reservoir in the municipality of Lavras da Mangabeira, located in the Salgado sub-basin, in the State of Ceará, Brazil, is the source used for several uses, including human consumption. Knowing the quality of the water, especially with regard to the trophic status index, is essential, as it indicates how the reservoir is in relation to eutrophication, which in turn, is related to possible releases of sewers and degrading activities in the area of influence of the weir. Therefore, the present study evaluated the trophic status of the reservoir, using the parameters chlorophyll-a, nutrient contents and primary production as indicators of the eutrophication process. Monitoring took place during the period from February 2016 to May 2018. To identify the degree of trophy, the Trophic State Index (TSI) was used through the method of Lamparelli (2004). To indicate the limiting nutrient, the nitrogen / phosphorus ratio (N: P) was used. The analyzes of total phosphorus and chlorophyll-a made it possible to calculate the average TSI and classify the source in the eutrophic category. The high concentrations of nutrients confirm the eutrophication of its waters, but do not imply the primary evolution, which involves the variation of other environmental factors. Comparing the results obtained from the analyzes with Resolution 357/05 CONAMA for class 2 water, values outside the established standards were obtained, with the exception of chlorophyll-a and total nitrogen. Phosphorus showed concentrations well above the environmental legislation, which directly influenced the degree of trophy in the reservoir.